PARTISIPASI MASYARAKAT DALAM IMPLEMENTASI EKSTRAKURIKULER DI SDN AIRLANGGA 1/ 198 SURABAYA - RUSDIANA DEVI, EVA; SETYOWATI, SRI (Inspirasi Manajemen Pendidikan, 2019)
Abstract This study aims to describe Forms The Constraints and Efforts and the Impact of Community Participation in Extracurricular Implementation. This study used to qualitative approach with the draft case study data collection techniques interviews observation and documentation. Research result show that 1 Forms of Community Participation there are four forms of participation given Finance Physical Morale Material. 2 The Constraints and Efforts for Community Participation as fallows a These Obstacles occur on the day of extracurricular as such Saturday due to school holiday the next constraints is Lack of care and trust form the student guardians and the last obstacle is on the infrastructure or school facilities to support implementation extracurricular activities b The Efforts made by the community in extracurricular were assisted by schools with the help of school committees and internal school residents to overcome obstacles to extracurricular implementation by coordinating all school activities including extracurricular using social media namely WhatsApp and Mediation on student guardians to solve problems and borrow public facilities to support extracurricular activities. 3 The Impact of Community Participation on schools students guardians and the community environment. The impact is the form of achievements behaviors and benefits of extracurricular implementation organized by other organizations / groups that participated in developing extracurricular activities at Airlangga Elementary School 1/198 Surabaya.Keywords community participation, extracurricularAbstrak: Penelitian ini bertujuan mendeskripsikan Bentuk Kendala dan Upaya dan Dampak Partisipasi Masyarakat dalam Implementasi Ekstrakurikuler di SDN Airlangga 1/ 198 Surabaya. Penelitian menggunakan pendekatan kualitatif rancangan studi kasus teknik yang digunakan wawancara observasi dan dokumentasi. Penelitian menghasilkan 1 Bentuk Partisipasi Masyarakat terdapat empat bentuk partisipasi yaitu Finansial Fisik Moril Material 2 Kendala dan Upaya Partisipasi Masyarakat menghasilkan 1 Kendala pada hari pelaksanaan kegiatan ekstrakurikuler yaitu hari sabtu karena hari libur sekolah kendala selanjutnya Kurang kepedulian dan kepercayaan wali murid dalam kegiatan ekstrakurikuler dan yang terakhir pada prasarana/fasilitas sekolah untuk menunjang implementasi ekstrakurikuler 2 Upaya dilakukan masyarakat dan sekolah dengan bantuan komite sekolah dan warga internal sekolah untuk mengatasi kendala-kendala implementasi ekstrakurikuler mengkoordinasikan semua kegiatan sekolah termasuk ekstrakurikuler dengan media sosial yaitu WhatsApp dan Mediasi pada wali murid untuk menyelesaikan permasalahan dan meminjam fasilitas umum untuk kegiatan ekstrakurikuler. 3 Dampak Partisipasi Masyarakat berdampak pada sekolah wali murid dan lingkungan masyarakat. Dampak tersebut berupa prestasi perilaku dan manfaat dari implementasi ekstrakurikuler yang diselenggarakan organisasi/kelompok lain yang ikut mengembangkan ekstrakurikuler di SDN Airlangga 1/ 198 Surabaya. Kata Kunci partisipasi masyarakat, ekstrakurikuler.